Measuring Unions’ Perceptions over Generations in Turkiye - Furkan Düzenli; Mehtap Demir (Sosyal Siyaset Konferansları Dergisi)
The foundations of unionization are known to have been laid down by blue-collar workers. However, with the inclusion of technology in work life these days in particular, things have not progressed as expected for unions. Blue-collar workers have typical characteristics, and when evaluated generationally, saying that blue-collar workers represent Generation X would not be wrong. With regard to work life, on the other hand, different generations are seen to have taken over the jobs that are considered to be for the new generation. When looking at Generation X, the unions that have known how to organize workers are have certain problems getting the new generation of employees to unite under the umbrella of an organization. This study aims to measure the perceptions toward unions of workers who are actively employed in the labor market in order to measure these perceptions in terms of generations so that unions can create their own strategies in the face of the changing perceptions arising from generational differences, with the aim being to fill the gap in the literature in this regard. For this purpose, the study uses quantitative analysis methods and analyzes the obtained data using the package program SPSS 22.00 in order to perform explanatory factor analysis, reliability analysis, the independent samples t-test, and one-way analysis of variance (ANOVA) in accordance with the hypotheses. Using the data obtained from 248 participants, the research has reveals the perceptions toward unions of employees from different generations to vary.